Governing the climate : new approaches to rationality, power and politics - Stripple, Johannes; Bulkeley, Harriet, 1972- (New York, NY : Cambridge University Press, 2014)
'Climate change is an issue that transcends and exceeds formal political and geographical boundaries. Social scientists are increasingly studying how effective policies on climate change can be enacted at the global level,'beyond the state'. Such perspectives take into account governance mechanisms with public, hybrid and private sources of authority. Studies are raising questions about the ways in which state authority is constituted and practiced in the climate arena, and the implications for how we understand the potential and limits for addressing the climate problem. This book focuses on the rationalities and practices by which a carbon-constrained world is represented, categorized and ordered. The book will enable investigations into a range of sites (e.g., the body, home, shopping centre, firm, city, forests, streets, international bureaucracies, financial flows, migrants and refugees) where subjectivities around climate change and carbon are formed and contested. Despite a growing interest in this area of work, the field remains fragmented and diffuse. This edited collection brings together the leading scholarship in the field to cast new light on the question of how, why, and with what implications climate governance is taking place. It is the first volume to collect this body of scholarship, and provides a key reference point in the growing debate about climate change across the social sciences'--
Introduction: on governmentality and climate change / Johannes Stripple and Harriet Bulkeley -- Part I. Governmentality, Critical Theory and Climate Change: 1. Bringing governmentality to the study of global governance / Eva L$1K6B(Bbrand and Johannes Stripple;s 2. Experimenting on climate governmentality with actor-network theory / Anders Blok; 3. Third side of the coin: hegemony and governmentality in global climate politics / Benjamin Stephan, Delf Rothe and Chris Methmann; 4. The limits of climate governmentality / Carl Death -- Part II. Cases of Climate Government: Theorizing Practice: 5. Neuroliberal climatic governmentalities / Mark Whitehead, Rhys Jones and Jessica Pykett; 6. Making carbon calculations / Sally Eden; 7. Smart meters and the governance of energy use in the household / Tom Hargreaves; 8. Translation loops and shifting rationalities of transnational bioenergy governance / Jarmo Kortelainen and Moritz Albrecht; 9. Governing mobile species in a climate-changed world / Juliet J. Fall; 10. Measuring forest carbon / Heather Lovell; 11. Climate security as governmentality: from precaution to preparedness / Angela Oels -- Part III. Future Directions: 12. The rise and fall of the global climate polity / Olaf Corry; 13. Climate change multiple / Samuel Randalls -- Conclusion: towards a critical social science of climate change? / Harriet Bulkeley and Johannes Stripple.
Includes bibliographical references and index.
Keywords: Global environmental change -- Government policy; Global environmental change -- International cooperation; Climatic changes -- Government policy; Climatic changes -- International cooperation; Environmental policy; Environmental policy -- International cooperation; LAW / Environmental; Climatic changes -- Government policy; Climatic changes -- International cooperation; Environmental policy; Environmental policy -- International cooperation; Global environmental change -- Government policy; Global environmental change -- International cooperation